The dark side of paclitaxel - Alekha K. Dash (Frontiers Media S.A., 2011)
The bark extract of Pacific Yew (Taxus brevifolia) was first reported to have anti-tumor activity in 1963. The active constituent responsible for this activity was later identified in 1971 as paclitaxel [1]. Paclitaxel is a cytotoxic drug used in the treatment of variety of tumors including ovarian, breast, and non-small-cell lung cancers...